Stereotaxic cutting of post-mortem human brains for neuroanatomical studies - García-Cabezas, Miguel Ángel; Pérez-Santos, Isabel; Cavada, Carmen (Frontiers in Neuroanatomy, 2023)
Stereotaxis is widely used in clinical neurosurgery, neuroradiosurgery, and neuroimaging. Yet, maps of brain structures obtained from post-mortem human brains are not usually presented in known stereotaxic coordinates. Post-mortem brain data given in stereotaxic coordinates would facilitate comparisons with in vivo human neuroimages and would also facilitate intra and inter-experiment comparisons. In this article, we present a crafted instrument for stereotaxic cutting of post-mortem human brain hemispheres. The instrument consists of a transparent methacrylate plate facing a mirror, four legs, and lateral regularly spaced columns permitting the insertion of large knives in-between the columns. This instrument can be built in any laboratory to obtain human brain slabs in the stereotaxic space of Talairach and Tournoux. We explain in detail the procedure for stereotaxic cutting of human brain hemispheres in the coronal plane, as well as the basis for calculating stereotaxic coordinates of histological sections obtained following the stereotaxic cutting protocol.